Антидискримінаційний закон у контексті формування етнонаціонального законодавства України - Вітман, Костянтин Миколайович; Витман, Константин Николаевич; Vitman, Konstantin (My University, 2012)
The modern phase of Ukrainian anti-discriminal law formation is analysed. The comparative analysis and classification of drafts of 2012 year are made. Recommendations and amendments to anti-discriminal law are proposed.
Вітман К. М. Антидискримінаційний закон у контексті формування етнонаціонального законодавства України / К. М. Вітман // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2012. – Т. 11. – С. 151-159.
Keywords: антидискримінаційне законодавство; види дискриминації; антидискриминационный закон; виды дискриминации; antidiscriminal law; forms of discrimination